KEYAKINAN HUKUM KARMA PHALA MEMODERASI PENGARUH SIFAT MACHIAVELLIAN DAN LOVE OF MONEY PADA KEPUTUSAN ETIS AUDITOR - Savitri, Ni Made Trisna; Wirakusuma, Made Gede; Dwirandra, A.A.N.B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to examine the effect of Machiavellian nature on auditors' ethical decisions, the effect of love of money on auditors' ethical decisions and the Law of Karma Phala in moderating the effect of Machiavellian nature and love of money on auditors' ethical decisions. This research was conducted at BPK RI Bali Province using primary data obtained from questionnaires. The method of determining the sample using the purposive sampling method with a sample of 44 auditors obtained. The data analysis technique used is the interaction test of the moderating variable moderated regression analysis (MRA). The implications of this research include two things, namely theoretical implications and practical implications. The results showed that Machiavellian nature had a negative effect on Auditor's Ethical Decisions, Love of money had a negative effect on Auditor's Ethical Decisions, and the Karma Phala Law variable was a moderating variable that weakened the influence of Machiavellian and Love of money on Auditor's Ethical Decisions.